TASAWUF DALAM ERA DIGITAL: Menjaga Kesadaran Spiritual di Tengah Arus Teknologi - Wahid, Annisa; Maskhuroh, Lailatul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Sufism, as one of the branches in Islamic tradition, plays a significant role in maintaining individual spiritual awareness. However, with the rapid advancement of digital technology, we find ourselves amidst a constant flow of information and distractions. The purpose of this research is to explore how Sufism can play a relevant role in this digital era to assist individuals in preserving their spiritual awareness. Additionally, this article highlights the importance of Sufism education in the digital era. This article involves conceptual analysis and literature review on Sufism and the impact of digital technology on spiritual awareness. The research findings indicate that the unavoidable technological wave can pose significant challenges for individuals who seek to maintain their spiritual awareness. Distortions of spiritual experiences, neglect of ethical values, and dependence on the virtual world can obscure the understanding and practice of Sufism. However, Sufism also offers relevant and beneficial tools to confront these challenges. Practices such as meditation, introspection, and self-control can assist individuals in strengthening their spiritual awareness in the digital era. Furthermore, a Sufi approach centered on the relationship with God and universal love can help individuals view technology as a tool that can be wisely utilized to enhance spiritual awareness, rather than a source of distraction.